Efektivitas Gamifikasi Berbasis AI dalam Pembelajaran Qira’ah Mutaqaddimah terhadap Literasi Digital dan Analisis Kritis - Balkis Nurjamilah; Gita Novita Fitri; Erlina Erlina (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The rapid development of digital technology demands a transformation in Arabic pedagogy within higher education. Qira’ah Mutaqaddimah courses frequently encounter barriers due to complex structures, unvocalized texts, and high student language anxiety. This study aims to evaluate the effectiveness of Artificial Intelligence-based gamification in enhancing digital literacy and critical reading analysis. The research employs a quantitative approach with a quasi-experimental design. The subjects involved thirty sixth-semester Arabic Language Education students at Universitas Islam Negeri Raden Intan Lampung, divided into experimental and control groups. Data were collected via questionnaires, classroom anxiety scales, and performance tests, then analyzed using paired sample t-tests. Quantitative analysis indicates significant improvements in the experimental class. The findings demonstrate that AI-driven gamification leads to a 37.28% increase in critical analysis, a 51.02% growth in AI literacy, and a 44.48% reduction in reading anxiety. Pedagogically, integrating AI and gamification serves as an effective instrument to modernize Arabic pedagogy, foster autonomous learning, and enhance students' critical thinking in the digital era.